Analysis of Raw Material Inventory Control with Using Economic Order Quantity (EOQ) Method - Adzaky, Muhammad Rafi; Erlina, Rr.; Ambarwati, Dwi Asri Siti (Journal of Business Management and Economic Development, 2024)
The Home Industry Karya Mandiri has struggled with inventory control, often resulting in excess raw materials. To address this issue, this research implements the Economic Order Quantity (EOQ) method as a strategic approach for optimizing raw material inventory, specifically coffee beans. The objective is to efficiently minimize total inventory costs. This descriptive quantitative research employs interviews and documentation for data collection, while the EOQ method is utilized for data analysis. This includes determining economic order quantities, order frequencies, safety stock levels, reorder points, and total inventory costs. Research findings indicate that applying the EOQ method reduced the frequency of raw material orders from 12 to 4 annually for the years 2022 and 2023. Consequently, it is projected that in 2024, Home Industry Karya Mandiri will maintain this order frequency, thereby preventing excess raw materials based on the actual needs data from 2022 and 2023. Additionally, the EOQ method successfully reduced total inventory costs by 48.58% in 2022 and 49.05% in 2023. Therefore, it is recommended that Home Industry Karya Mandiri continue utilizing the EOQ method for effective raw material inventory control.